2020
DOI: 10.1108/jes-05-2020-0233
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the informal economy in Western Europe: beyond a rational economic actor perspective

Abstract: PurposeThe dominant theorisation of the informal economy views participants as rational economic actors operating in the informal economy when the expected benefits exceed the perceived costs of being caught and punished. Recently, an alternative theory has emerged which views participants as social actors operating in the informal economy due to their lack of vertical trust (in governments) and horizontal trust (in others). The aim of this paper is to evaluate these competing theorisations.Design/methodology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Various participants would admit outright that they paid bribes for working permits, employed their workers informally without paying taxes and/or were evading value added taxes. Informal behaviours were thus more or less normalised, which is in line with the literature that shows that the informal economy in some contexts is rather the norm and not the exception (Williams & Oz-Yalaman, 2021).…”
Section: Sensitivity Of Topics As An Emerging Issue: Influence Of Pos...supporting
confidence: 88%
“…Various participants would admit outright that they paid bribes for working permits, employed their workers informally without paying taxes and/or were evading value added taxes. Informal behaviours were thus more or less normalised, which is in line with the literature that shows that the informal economy in some contexts is rather the norm and not the exception (Williams & Oz-Yalaman, 2021).…”
Section: Sensitivity Of Topics As An Emerging Issue: Influence Of Pos...supporting
confidence: 88%
“…This paper advances the literature on informal economies (Bruton Ireland and Ketchen, 2012;ILO, 2018;Galdino et al, 2018;Godfrey, 2011;McGahan, 2012;Schneider, 2012;Webb et al, 2014;Williams and Oz-Yalaman, 2020). As far as the author knows, this is the first study to investigate pricing methods within the informal economy.…”
Section: Theoretical Implicationsmentioning
confidence: 59%
“…Informal economies are prevalent and highly researched (Bruton et al, 2012;ILO, 2015;Galdino et al, 2018;Godfrey, 2011;McGahan, 2012;Schneider, 2012;Webb et al, 2014;Williams and Oz-Yalaman, 2020). These are economies comprising groups governed by socially shared and unwritten rules and who function outside of officially regulated channels (Helmke and Levitsky, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The distrust to public institutions also serves as a motivational factor for the informal economy (Webb et al, 2013). It is even revealed that higher chances to be caught or harsher punishments do not impact the level of the informal economy, whereas the level of trust in the government does (Williams & Oz-Yalaman, 2020). Some social informal groups with its own rules and informal economic activities are will be used to substitute weak public social protection mechanisms (Stavropoulou, Holmes & Jones, 2017).…”
Section: ) Theoretical Backgroundmentioning
confidence: 99%